Taxonomic status of southern South American Conepatus (Carnivora: Mephitidae) - Schiaffini, Mauro Ignacio (2013)
Despite recent taxonomic evaluations of Mephitidae and North American hog-nosed skunks, southern South American species of Conepatus have not been thoroughly examined in a systematic context. Conepatus chinga and Conepatus humboldtii were described more than 150 years ago, based on external characters such as hair coloration and size. Although historically recognized as valid species, to date no detailed systematic analysis has been performed for either of these taxa. Herein, we evaluated the taxonomic status of C.chinga and C.humboldtii within the southern part of South America using geometric morphometrics of the skull and mandible, mitochondrial DNA analysis using the cytochrome b and cytochrome oxidase c subunit I genes, and also control region and pelage pattern variation. We failed to find morphological (skull shape and pelage coloration patterns) or molecular differences between these two species; thus, we considered that the specimens assigned to C.chinga and C.humboldtii belong to the same species. Our results indicate that environmental variation seems to be responsible for shape and size variation in Conepatus skulls from southern South America.